Management of uncomplicated malaria in private health facilities in North-West Ethiopia: a clinical audit of current practices - Mesele Damte Argaw; Thandisizwe Redford Mavundla; Kassa Daka Gidebo (BMC, 2019)
Abstract Background Malaria is one of the leading public health problems in sub-Saharan Africa that contributes to significant patient morbidity and mortality. The aim of the study was to investigate adherence to malaria diagnosis and treatment guidelines by private health sector providers and compare their performance against the public private partnership (PPP) status. Methods A facility-based retrospective clinical audit was conducted between October 2016 and January 2017 in 11 medium clinics in the West Gojjam zone of the Amhara Region, North-west Ethiopia. Data was extracted from patient medical records using pretested data abstraction forms. Descriptive statistics were employed to present the findings and adherence of health workers against the national and international standards were classified as ideal, acceptable, minor error and major error for both malaria diagnosis and treatment. A chi-square (X2) test was used to test for a statistically significant relationship after the data had been categorized using public private partnership status at P < 0.05. Results One thousand six hundred fifty clinical files were audited. All malaria suspected patients were investigated either with microscopy or rapid diagnostics test (RDT) for parasitological confirmation. The proportion of malaria treated cases was 23.7% (391/1650). Of which 16.6% (274/1650) were uncomplicated, 3.69% (61 /1650) were severe and complicated and the rest 3.39% (56/1650) were clinical diagnosed malaria cases. And the malaria parasite positivity rate was 20.30% (335/1650). All malaria suspected patients were not investigated with ideal malaria diagnosis recommendations; only 19.4% (320/1650) were investigated with acceptable malaria diagnosis (public private partnership (PPP) 19.4%; 176/907; and non-public private partnership (NPPP) 19.38%; 144/743, X2 (1) = 0.0With regards to treatments of malaria cases, the majority 82.9% of Plasmodium vivax cases were managed with ideal recommended treatment (X2 (1) = 0.35, P = 0.55); among Plasmodium falciparum, mixed (Plasmodium falciparum and Plasmodium vivax). Conclusion The clinical audit revealed that the majority of malaria patients had received minor error malaria diagnostic services. In addition, only one fifth of malaria patients had received ideal malaria treatment services. To understand the reasons for the low levels of malaria diagnosis and treatment adherence with national guidelines, a qualitative exploratory descriptive study is recommended.